2011
DOI: 10.1242/bio.2011023
|View full text |Cite
|
Sign up to set email alerts
|

Wnt signalling antagonizes stress granule assembly through a Dishevelled-dependent mechanism

Abstract: SummaryCells often respond to diverse environmental stresses by inducing stress granules (SGs) as an adaptive mechanism. SGs are generally assembled as a result of aggregation of mRNAs stalled in a translational pre-initiation complex, mediated by a set of RNA-binding proteins such as G3BP and TIA-1. SGs may serve as triage centres for storage, translation re-initiation or degradation of specific mRNAs. However, the mechanism involved in the modulation of their assembly/disassembly is unclear. Here we report t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
23
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 17 publications
(26 citation statements)
references
References 50 publications
2
23
0
Order By: Relevance
“…In NIH3T3 cells, Wnt signaling triggers Dvl-dependent activation of the Rac1 GTPase. Activated Rac1, in turn, inactivates the RhoA GTPase to inhibit SG assembly 67 . Thus, Wnt signaling antagonizes SG assembly.…”
Section: Rho Gtpase Signalingmentioning
confidence: 99%
“…In NIH3T3 cells, Wnt signaling triggers Dvl-dependent activation of the Rac1 GTPase. Activated Rac1, in turn, inactivates the RhoA GTPase to inhibit SG assembly 67 . Thus, Wnt signaling antagonizes SG assembly.…”
Section: Rho Gtpase Signalingmentioning
confidence: 99%
“…The images were acquired using ImageQuant LAS 4000 (GE Healthcare). EZview TM Red Anti-HA Affinity beads (Sigma) and rabbit GFP antibody [86]-bound protein A beads (Invitrogen) were used for immunoprecipitation of HA-and GFPtagged proteins, respectively.…”
Section: Immunoprecipitation and Western Blottingmentioning
confidence: 99%
“…Rabbit anti-GFP (1:10,000) and rabbit anti-Nup358 (1:3,000) antibodies have been described earlier [25,86].…”
Section: Immunoprecipitation and Western Blottingmentioning
confidence: 99%
“…We looked for a relationship between the function of stress granules and somite development in zebrafish and found that P97a and P97b, homologous proteins to the translation initiation factor eIF4G, are components of stress granules and both are required in zebrafish for mesoderm formation (Nousch et al, 2007). At the same time we found that the mammalian Disheveled (Dvl) protein, an effector of the Wnt signaling pathway, negatively regulates the assembly of stress granules (Sahoo et al, 2012) and it is known that the Wnt pathway is involved in zebrafish somite formation (Bajard et al, 2014). …”
Section: Discussionmentioning
confidence: 99%
“…Important reservoirs for mRNAs are the RNA granules, which include P-bodies (Oh et al, 2013; Parker and Sheth, 2007), stress granules (Anderson and Kedersha, 2008; Kedersha et al, 2002; Sahoo et al, 2012), germ granules (in germ cells) (Updike and Strome, 2010), and other types of RNA-containing cytoplasmic foci. This classification of RNA granules is based on their composition, size and cell of origin.…”
Section: Introductionmentioning
confidence: 99%